Peliosis hepatis – an unusual radiological presentation with diagnosis made easy: A case report (Indian Journal of Case Reports, 2024)
Peliosis hepatis (PH) is a condition affecting the liver causing sinusoidal proliferation resulting in cavity formation. It is benign and a rare condition. It can be incidentally detected or the patient can present complications secondary to it such as hepatic failure, abdominal distension due to hepatomegaly, ascites, and hemoperitoneum. Imaging findings can be misinterpreted as other conditions such as polycystic liver disease, hemangioma, hepatocellular carcinoma, angiosarcoma, and metastases. That is why, it is important to differentiate all these conditions. Imaging plays a crucial role. Here, we report a case of a 30-year-old woman who came with abdominal distension as her primary complaint was diagnosed to have this condition after carefully ruling out other conditions. She had multiple cystic blood filled and hemorrhagic cavitating liver lesions on imaging. Diagnosis of PH was made. The lesion was not biopsied as there was an increased risk of bleeding. The patient succumbed soon after. PH is a benign condition that is possible to diagnose and differentiate from other liver lesions on imaging based on the obvious findings as seen in our case thus simplifying diagnosis and avoiding biopsy in a vascular cavitatory lesion.